Modelagem comparativa e triagem virtual hierárquica para identificação de moduladores das OBPs de Lutzomyia Longipalpis - Santana, Isis Bugia (2016)
The Visceral Leishmaniasis (VL) is the second most important vector-borne disease in the world, transmitted in the Americas by Lutzomyia longipalpis, vector control is essential for the prevention of the disease. But since it is not possible to identify the oviposition sites, the fight is directed to adult insects, using traps impregnated with chemical attractants. Whereas the Odorant Binding Proteins (OBPs) act in the first level of odor selection, this work used in silico methodology to identify putative vector olfactory chemical modulators based on the structure of OBPs and known ligands. For this, tridimensional (3D) structure of L. longipalpis OBPs were predicted by three comparative modeling methods. The best model, predicted by I-Tasser, was refined by Molecular Dynamics on Gromacs. Then, in a hierarchical virtual screening approach, natural compounds of ZINC12 closer to the typical OBP ligands in global chemical space, provided by ChemGPS-NP, were evaluated and staggered concerning affinity with the orthosteric site from the OBP, by molecular docking on DOCK6. The compounds were scored by GRIDSCORE, then the 100 best classified were submitted to AMBERSCORE, which took into account the flexibility from both OBP and the docked ligands. The lowest energy conformations interacted with a hydrophobic pocket through residues Met6, Gly10, Glu11, Ala9 Arg14, Leu74, Met53, Phe118, Phe119, Pro120, amino groups and formed ionic interaction with carboxyl of Glu11, Furthermore, Phe119, Asn29 and Gln69 formed hydrogen bonds, this last formed donor and acceptor H-bonds.